EVALUATION OF HARVEST AGE ON PHYSICOCHEMICAL PROPERTIES AND ANTIOXIDANT CAPACITY OF BUTTERNUT PUMPKIN FLOUR - Siti Nurdjanah; Ika Mulawati; Tanto Pratondo Utomo; Fibra Nurainy (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Processing pumpkins (Cucurbita moschata) is one alternative to prolong its shelf life and to provide flexibility in uses.. The aim of this research was to find the right harvest time to produce pumpkin flour with high yield and good quality. The experiment was designed using a complete randomized block design with 4 replications. The treatments included the harvest age of 15, 20, 25, and 30 days after fruit set (DAFS). The data obtained were processed using ANOVA, and continued tested using DMRT. The pumpkin with various maturity levels was analysed for starch, moisture, ash, lipid, protein and carotenoid contents. Yield, potential as antioxidant, granular shape and size were also determined The results indicate that pumpkin harvested at 25 DAFS produced high yield and good quality flour.